Determinants of Indonesian fifth graders' learning motivation: A survey study - Gede Margunayasa, I; Gede Astawan, I; Made Citra Wibawa, I; Redan Werang, Basilius (Edelweiss Applied Science and Technology, 2024)
Motivation serves as a powerful catalyst for positive change, influencing various aspects of life such as health, employment, and societal well-being, particularly in the context of learning and academic achievement. This study aimed to describe the impact of school environment and teacher morale on the learning motivation of fifth graders in the elementary schools of Buleleng District, Bali, Indonesia. A quantitative research approach using a survey research design was employed to attain this objective. Research data were obtained from a total of 219 fifth graders at the elementary schools in the surveyed area. Obtained data were subjected to a rigorous statistical analysis using simple and multiple linear regression analysis techniques utilizing the SPSS software version 21. The results of the data analysis indicate that both the school environment and teacher morale have a significant and positive impact on the learning motivation of fifth graders in the surveyed elementary schools, whether considered individually or together. These findings underscore the importance of fostering a positive school environment and strong teacher-student relationships to enhance student motivation and academic success. This study contributes to the existing literature by emphasizing the crucial role that teacher-student relationships play in creating a supportive and motivating learning environment. Therefore, strengthening these relationships is essential for improving student motivation and academic performance.